Programmed death-ligand 1 (PD-L1) characterization of circulating tumor cells (CTCs) in muscle invasive and metastatic bladder cancer patients. Issue 1 (December 2016) - Anantharaman, Archana; Friedlander, Terence; Lu, David; Krupa, Rachel; Premasekharan, Gayatri; Hough, Jeffrey; Edwards, Matthew; Paz, Rosa; Lindquist, Karla; Graf, Ryon; Jendrisak, Adam; Louw, Jessica; et al.
Abstract Background While programmed death 1 (PD-1) and programmed death-ligand 1 (PD-L1) checkpoint inhibitors have activity in a proportion of patients with advanced bladder cancer, strongly predictive and prognostic biomarkers are still lacking. In this study, we evaluated PD-L1 protein expression on circulating tumor cells (CTCs) isolated from patients with muscle invasive (MIBC) and metastatic (mBCa) bladder cancer and explore the prognostic value of CTC PD-L1 expression on clinical outcomes. Methods Blood samples from 25 patients with MIBC or mBCa were collected at UCSF and shipped to Epic Sciences. All nucleated cells were subjected to immunofluorescent (IF) staining and CTC identification by fluorescent scanners using algorithmic analysis. Cytokeratin expressing (CK)+ and (CK)− CTCs (CD45−, intact nuclei, morphologically distinct from WBCs) were enumerated. A subset of patient samples underwent genetic characterization by fluorescence in situ hybridization (FISH) and copy number variation (CNV) analysis. Results CTCs were detected in 20/25 (80 %) patients, inclusive of CK+ CTCs (13/25, 52 %), CK− CTCs (14/25, 56 %), CK+ CTC Clusters (6/25, 24 %), and apoptotic CTCs (13/25, 52 %). Seven of 25 (28 %) patients had PD-L1+ CTCs; 4 of these patients had exclusively CK− /CD45− /PD-L1+ CTCs. A subset of CTCs were secondarily confirmed as bladder cancer via FISH and CNV analysis, which revealed marked genomic instability. Although this study was not powered to evaluate survival, exploratory analyses demonstrated that patients with high PD-L1+ /CD45− CTC burden and low burden of apoptotic CTCs had worse overall survival. Conclusions CTCs are detectable in both MIBC and mBCa patients. PD-L1 expression is demonstrated in both CK+ and CK− CTCs in patients with mBCa, and genomic analysis of these cells supports their tumor origin. Here we demonstrate the ability to identify CTCs in patients with advanced bladder cancer through a minimally invasive process. This may have the potential to guide checkpoint inhibitor immune therapies that have been established to have activity, often with durable responses, in a proportion of these patients.